Decisions and dissents of Justice Ruth Bader Ginsburg : a selection - Ginsburg, Ruth Bader; Brettschneider, Corey Lang. (New York : Penguin Books, 2020)
"The trailblazing Supreme Court Justice Ruth Bader Ginsburg in her own words. Her most essential writings on gender equality and women's rights, reproductive health care, and voting and civil rights"-- Provided by publisher.
Brief for the Appellant in Reed v. Reed (1971) -- Brief Amicus Curiae on Behalf of the American Civil Liberties Union in Craig v. Boren (1976) -- Majority Opinion in United States v. Virginia (1996) -- Dissenting Opinion in Lily Ledbetter v. Goodyear Tire Company (2007) -- Brief for the Petitioner in Struck v. Secretary of Defense (1972) -- Dissenting Opinion in Gonzales v. Carhart (2007) -- Dissenting Opinion in Burwell v. Hobby Lobby Stores, Inc. (2014) -- Concurring Opinion in Whole Woman's Health v. Hellerstedt (2016) -- Dissenting Opinion in Adarand Constructors v. Pena (1995) -- Majority Opinion in Olmstead v. L.C. (1999) -- Dissenting Opinion in Bush v. Gore (2000) -- Dissenting Opinion in Ricci v. Destefano (2009) -- Dissenting Opinion in Shelby County v. Holder (2013)
Includes bibliographical references.
Keywords: Dissenting opinions -- United States; Judicial opinions -- United States; Law -- United States -- Cases